(untitled) (International Journal of Innovative Technologies in Economy, 2025)
The digital age has drastically altered how we go about our daily lives, jobs, and social interactions. Major changes have occurred in communication methods and information dissemination, demonstrated by increased internet usage to access social media. Social media is an online platform that supports individual creativity and ideas and enables long-distance communication such as the TikTok platform. This study aims to determine whether Live streaming and Free Shipping influence Impulse Buying Thrifting TikTok Shop. The research employs a quantitative methodology. Information was gathered via online surveys conducted with customers from the Cirebon city region who had bought secondhand fashion items. Random sampling method was used for sampling and Hair formula calculation obtained 150 respondents. Structural Equation Modeling - Partial Least Square (SEM-PLS) was utilized for the analysis. It was found from the results that Live Streaming and Free Shipping both play a significant role in influencing Impulse Buying. This shows that both independent variables together influence consumer minds to make impulsive purchases of TikTok Shop thrifting products with a stronger influence on Impulse Buying obtained from the Free Shipping variable. This shows that Free shipping allows influencing consumer minds to buy thrifting products impulsively, because Free Shipping reduces additional costs that often become buyer considerations when buying something. The results show that combining interactive features such as live streaming and economic incentives such as free shipping can create a shopping environment that encourages impulsive shopping activities, especially for products purchased through hunting. Therefore, in the technology-based economy era, marketing strategies that focus on interactivity and cost incentives are very important to increase sales rates on digital platforms.